2012
DOI: 10.1590/s1983-40632012000400004
|View full text |Cite
|
Sign up to set email alerts
|

Doses de potássio em cobertura na cultura da abóbora

Abstract: Embora existam recomendações de adubação para o cultivo comercial de abóbora, são escassos os trabalhos que relacionam o efeito da adubação potássica em cobertura à produtividade desta cultura. Assim, este trabalho foi conduzido com o objetivo de avaliar doses de potássio em cobertura, na produção de frutos de abóbora (híbrido Mirian), em fazenda experimental da Universidade Estadual Paulista "Júlio de Mesquita Filho", em São Manuel (SP). O delineamento experimental foi em blocos casualizados, com cinco tratam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
3
11
1
11
Order By: Relevance
“…For yield, an increasing linear model fitted to the data, with R 2 = 0.95, and the maximum value (35,870.61 kg ha -1 ) was obtained in the field for the highest K 2 O dose (300 kg ha -1 ) ( Figure 2B). Araújo et al (2012), working with squash, obtained results higher than those of the present study (9.681 g per plant) applying a K 2 O dose estimated at 199 kg ha -1 . On the other hand, Genuncio et al (2010) reported significant effect (linear model) on fruit mass, in the cultivation of tomato in protected environment, for the application of K through fertigation.…”
Section: Resultscontrasting
confidence: 90%
See 3 more Smart Citations
“…For yield, an increasing linear model fitted to the data, with R 2 = 0.95, and the maximum value (35,870.61 kg ha -1 ) was obtained in the field for the highest K 2 O dose (300 kg ha -1 ) ( Figure 2B). Araújo et al (2012), working with squash, obtained results higher than those of the present study (9.681 g per plant) applying a K 2 O dose estimated at 199 kg ha -1 . On the other hand, Genuncio et al (2010) reported significant effect (linear model) on fruit mass, in the cultivation of tomato in protected environment, for the application of K through fertigation.…”
Section: Resultscontrasting
confidence: 90%
“…The linear model obtained for yield in the present study may be associated with the large demand of vegetable crops for K, which is the macronutrient most extracted by the majority of these plants (Araújo et al, 2012), as confirmed by the studies of Silva et al (2013), with pumpkin, Silva Júnior et al (2006), with melon, and Nogueira et al (2014), with watermelon.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Os dados obtidos de massa seca (MS) comportaram-se de forma linear na equação de regressão, representando um acúmulo máximo de 3,10 kg de massa seca nos frutos com dose de 240 kg K 2 O ha -1 (figura 4). Araújo et al (2012), em estudo com doses de potássio em cobertura na cultura da abóbora, observaram um acúmulo de massa seca nos frutos de 1,870 kg com dose 400 kg K 2 O ha -1 . Veloso et al (2001) observaram efeito significativo na aplicação de potássio isoladamente e na interação entre a calagem e o potássio na massa fresca de frutos de abacaxi cultivar 'Pérola'.…”
Section: Resultsunclassified